Educação domiciliar no Brasil: quem ganha, quem perde. Uma análise política e jurídica frente ao direito à educação - Mata, Mardeli Maria da (2022)
This study is carried out within the scope of the State, Policies and Management of Education Research Line and starts from the following questions: to what extent is homeschooling institution a right of choice for parents. Whose is the right to educate? Can school education be flexible? Who is interested in homeschooling? What are its theoretical bases and conceptions? In this sense, our general objective is to analyze the proposal of homeschooling in Brazil from the perspective of the right to education. As for our specific objectives, we seek to: understand the concept of public policies and its relationship with the neoliberal state and its influence on education; present the main public educational policies in Brazil, after the CF of 1988, trying to understand whether the institution of homeschooling, according to the intentions of the federal government, may or may not be legitimately considered as an educational policy; understand the right to education in Brazil as a social right based on the historicity of our Constitutions and its relationship with the school, highlighting the main infra-constitutional norms; identify the origin, concept, bases and theoretical conceptions of homeschooling, highlighting its theoretical foundations and presenting the law projects that are being processed in the National Congress for its institution, as well as the decision of the Federal Supreme Court handed down in the Extraordinary Appeal nº 888.815/LOL in which the possibility and constitutionality of homeschooling was discussed, seeking to understand whether or not compulsory schooling can be made more flexible. A bibliographic research was carried out from the authors Apple (2003), Azevedo (2004), Cury (2017; 2019), Saviani (2004; 2007, 2018, 2019), Laval (2019), among others, in addition to research and document analysis of the Brazilian Constitutions, the infraconstitutional legislation on education, the law projects and the decision of the STF. By using the results of this research, we aim to contribute to a broader knowledge of education, school and public educational policies, regarding the right to education, seeking a more in-depth study on homeschooling, origin and foundations to understand the real reason for the proposal of its institution by the federal government, which defends it as a public educational policy, in the name of the effectiveness of the right to education, but which carries out several actions following the neoliberal bias. It is essential to defend the school as an institution, the defense of the rights of children and adolescents to receive an education from a democratic perspective, forming citizens who are aware of their social role.